Avaliação de desempenho de recobrimentos em ferramentas de metal duro no torneamento do aço ABNT 4340 temperado por meio de sinais de emissão acústica - Luís Henrique Andrade Maia (2015)
The field of manufacturing processes is of utmost importance to the economy of industrialized countries where competition dictates market parameters. The use of cheaper and more resistant materials and the decrease in manufacturing time are targets of constant studies in contemporary engineering. Within this scenario, the principal aim of this work is to study the behavior an acoustic emission (AE) signals used to identify tool wear mechanisms in coated tungsten carbide employed in turning of hardened AISI 4340 steel (46 ±1 HRc). Therefore, it’s described the characteristics of the tools to assess the composition and phases of the substrate and coatings. Additionally, tensile tests were conducted to determine how the acoustic emission signal behaves in relation to the elastic and plastic deformation and fracture. Turning tests were conducted using cemented carbide tools with and without the common AlCrN coatings of nanostructured base and then evaluated AE signals and the performance of the tools during operation. The dried at turning tests were performed using the following cutting parameters: Cutting speeds (vc) of 150 m/min 200 m/min and 250m/min; feed rates (f) of 0.10 mm/rev, 0.15 mm/rev and 0.20 mm/rev and depths of cut (ap) of 0.25 mm and 0.75 mm. Finally the techniques knows as short time Fourier transform (STFT) and the spectral power density (PSD) were used to characterize the tools and the analysis of AE signals and correlated to the wear mechanisms and tool performance. The results showed that the acoustic emission signals are sensitive to tool wear, especially at low and moderate cutting conditions. Coating failures were also identified using the technique, showing a decrease in life of tools and a variation in the amplitudes of the signals.